Information and communication technology (ICT) education in the city school, Pakistan - A success story in the large-scale introduction of the UK National Curriculum's ICT component in Pakistan - Ali, I.; Proctor, J. (Aslib Proceedings, 2005)
Purpose - In an age of information technology some developing countries are more vulnerable than others to international competition through failure to utilize fully the benefits of an ICT culture. The authors suggest that the strategies in response must include a radical review of attitudes and methods of delivery of ICT in schools and give as an example the recent experience of The City School, the nationwide schools' organisation in Pakistan with whom they are employed. Design/methodology/approach - The authors review the current position of ICT in schools in Pakistan and suggest as a model of development, for schools of a corresponding standing, that of The City School. They describe how The City School responded to ICT, ensuring that all its pupils would have access to the most modem of ICT courses. Discusses how the decision to implement a complete change, or revolution, in teaching ICT was brought about in a relatively short time. It discusses the nature of the programme, how it was organised, the materials required and the outcomes of its implementation including its outstanding success with pupils and their parents. Findings - The authors chronicle the historical developments within The City School that brought about radical change within a comparatively short period and identify careful planning, training, and the motivation of stakeholders, i.e. pupils, teachers and parents, as key elements in its successful implementation. Originality/value - The authors suggest that The City School experience provides a model that may be emulated by schools elsewhere in both developing and industrially developed countries.
Keywords: Pakistan; communication technologies; design and development; schools

Improving Educational Quality through Interactive Radio Instruction - World Bank (2005)